Quality assurance and accreditation in distance education and e-learning : models, policies and research - Jung, Insung, 1959-; Latchem, C. R. (Colin R.); Herrington, Jan. (New York : Routledge, 2012)
'Drawing on the knowledge and experience of leading managers, practitioners and researchers, research and case studies, this book provides a unique and comprehensive analysis of Quality Assurance (QA) concepts, approaches, models, issues, practices and research in ODL and ICT worldwide. The book is global in scope and covers both the developed and developing world. It considers the theory, research and practice of policy-making and implementation in QA and accreditation, and also the institutional and cultural acceptability of QA as well as the areas regarded as problematic. With the growth of cross-border education, institutions must provide evidence of the quality of their courses, teaching, learning and management systems for national and international accreditation. This exposes them to rigorous external review and requires their conformity with national and international regulatory environments and benchmarks. It also increases their awareness of, and responsiveness to, national and global quality standards. This edited collection provides policy-makers, ODL researchers, and Higher Education administrators with an invaluable resource on QA and accreditation models and policies from around the World'-- Provided by publisher.
'Quality assurance (QA) in online and distance learning (ODL) is a contentious issue. Some argue that the same standards from face-to-face education should apply, while others say that ODL demands its own specific guidelines and standards. Some providers may look upon QA as an imposition of corporatization and bureaucracy, while others see it as a means of establishing a culture of quality. With the growth of cross-border education, institutions must provide evidence of the worth of their services in order to be accredited. This exposes them to rigorous external review and requires conformity with national and international regulatory environments and benchmarks. Until now, however, there has been a lack of research-based literature to guide those looking to better understand the implementation of QA in ODL. Quality Assurance and Accreditation in Distance Education and E-learning explains what is involved in QA and accreditation in education in open, distance, dual-mode, and conventional universities in both the developed and the developing world. The book is edited and authored by experts with extensive international experience in ODL, e-learning, and QA who give careful consideration to the possibilities and challenges involved. Providing unique analysis of the concepts, approaches, models, issues, practices, theory and research, this book is an invaluable guide for all policy-makers, managers, practitioners, and researchers in the field'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Distance education -- Standards; Accreditation (Education); Quality assurance